Analysing the Impact of Corruption on the Effectiveness of Law Enforcement: A Case Study in Police Science Studies in Indonesia - Wibison, Pendi -; Nita, Surya; Badry, Ahmad Ibrahim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Corruption has become a profound issue in the context of law and policing in Indonesia. This article aims to analyse the impact of corruption on the effectiveness of law enforcement, with a focus on the study of police science in Indonesia. The method used is a literature review, by collecting and analysing various related literature, reports and case studies. The results of the literature analysis show that corruption within the police has a significant impact on various aspects of law enforcement. Corruption can hamper the integrity and credibility of the police institution, affect the investigation process, and potentially damage the relationship between the police and the community. Case studies in the Indonesian context reveal the challenges faced in efforts to eradicate corruption in the police. In addition, this article also discusses the efforts that have been made by the government and relevant institutions in addressing the issue of corruption in the police. These include policy reforms, training, and stricter law enforcement against perpetrators of corruption. In order to improve the effectiveness of law enforcement in Indonesia, concrete steps are needed in the prevention and eradication of corruption in the police. The results of this literature analysis provide deep insight into the complexity of corruption issues in the context of policing, as well as identifying directions for further research in an effort to improve the integrity and efficiency of law enforcement agencies in Indonesia.